소백산국립공원 삼가지구 관속식물의 고도별 분포패턴 - 박환준; Hwan Joon Park; 안지홍; Ji Hong Ahn; 서인순; In Soon Seo; 이새롬; Sae Rom Lee; 이병윤; Byoung Yoon Lee; 김중현; Jung Hyun Kim (한국산림과학회지, 2020)
소백산국립공원 삼가지구 관속식물의 고도별 수직분포 및 분포변화를 파악하기 위해 삼가탐방지원센터(400 m)에서 정상(1,439 m)까지 해발 100 m 단위로 등분하여 11개 구간에 대한 식물목록을 작성하였다. 현지조사를 실시한 결과 92과 235속 332종 3아종 37변종 3품종 총 375분류군이 출현하였다. 구간별 식물 종다양성 패턴을 분석한 결과, 고도가 증가함에 따라 점차 종다양성이 감소하다가 특정구간에서 증가하는 역단봉형 패턴이 나타났다. 고도에 따른 종 분포패턴과 치환성 양이온 Ca 2+ , Mg 2+ 와 토양 pH, 유효인산, 온량지수, 조사면적 등의 환경요인이 양의 상관관계를 보였고 경사, 토양 수분, 치환성 양이온 Na 2+ 이 음의 상관관계를 보였다. DCA 분석 기법을 이용하여 구간별 식분의 분포를 분석한 결과 Ⅰ,Ⅱ축 상에서 2개의 그룹으로 구분되었다. 구간별 식분의 배치는 400∼500 m 구간부터 1400∼1500 m 구간까지 순차적으로 배열되었다. 이러한 식분의 배치에 영향을 미치는 환경요인은 토양 수분, pH, K 2+ , Na 2+ , 유효인산, 경사도 등 토양 및 지형적 요인으로 나타났다. 생물다양성 보전, 지속가능한 이용에 있어서 본 연구 결과는 중요한 기초자료로서 역할을 할 것으로 기대되며, 식물종들의 생태·환경적 특징과, 분포범위를 파악하기 위해서는 지속적인 모니터링과 함께 관련 연구들을 지속적으로 발전시켜야 할 것이다. In order to evaluate the vertical distribution and distributional pattern of vascular plants in the Samga district of Sobaeksan National Park, vascular plants were surveyed along a hiking trail from the Samga Tour Support Center to the top of a mountain. The elevation range was divided into 11 sections with 100 m intervals from 400 m to 1439 m above sea level.A total of 375 taxa were listed, comprising 92 families, 235 genera, 332 species, 3 subspecies, 37 varieties, and 3 forms. The pattern of species richness along theelevational gradient showed a reverse hump-shaped trend. The species distribution pattern was positively correlatedwith the soil exchangeable cations Ca 2+ and Mg 2+ , soil pH, available phosphate, and the warmth index. Furthermore, slope, soil moisture content, and soil exchangeable cations were significantly correlatedwith species distribution. DCA grouped herb species into two groups. Stands of each section were sequentially arranged from 400 m to 1500 m along an altitudinal gradient. Soil moisture content, soil pH, soil K 2+ and Na 2+ , available phosphate, and slope were significantly correlated with stand distribution. This study provides important data that could be useful for conservation and the sustainable use of biodiversityin the study area. In order to understand the ecological and environmental characteristics and distribution of plant species, it will be necessary to continuously develop relative studies with continuous monitoring.